(untitled) (International Seven Journal of Multidisciplinary, 2023)
The general objective of the research was "To analyze the importance of didactic strategies based on moral values for coping with bullying in second year students of General Basic Education (EGB) of the Siete de Octubre Educational Unit". The methodology had a mixed approach, where qualitative methods and techniques were applied, an instrument composed of 13 questions was used, which were applied to a sample of 73 students of second year of EGB, an interview was also contemplated, which was carried out to two teachers of the institution, who were consulted about cases of bullying and the actions or methodological strategies used by the institution and the teaching staff. The results obtained show that many of the students are not satisfied with the didactic strategies used, which are considered not to have been effective since there have been cases of bullying, the interview allowed corroborating the perception of the students, since, didactic strategies based on moral values have not been implemented, that is why various activities such as games, group activity are proposed, which allow improving school coexistence and achieving an assertive communication of the students.